1995
DOI: 10.1074/jbc.270.28.16719
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Peptide Isomerase from Funnel Web Spider Venom

Abstract: A novel peptide isomerase was purified from the venom of funnel web spider, Agelenopsis aperta. The complete primary structure of the isomerase has been established by sequence analyses of polypeptide chains, assignments of disulfide bridges, carbohydrate analyses, and mass spectrometry of sugar chains. The isomerase was found to be a 29-kDa polypeptide that consists of an 18-residue light chain and a 243-residue heavy chain connected by a single disulfide bridge. The heavy chain contains three intramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 15 publications
1
62
0
1
Order By: Relevance
“…5A) or with a mixture of 1 ,uM w-conotoxin MVIIC, 1 ,iiM w-conotoxin GVIA, and 0.2 ,iiM agatoxin TK (Fig. 6A), confirming that the depolarization-induced increases in [Ca2~I, resulted from the opening of voltage-gated Ca2~channels (Nachshen and Blaustein, 1979;Dunlap et al, 1995) largely belonging to the N-, P-, and Qtype family of channels in view of the selectivity of the toxins used (Rivier et al, 1987;Hillyard et al, 1992;Shikata et al, 1995). (In preliminary experiments, we tested a broad variety of Ca2~channel toxin combinations and found that the mixture used in the present study was the most effective in blocking K ±-induced changes in [Ca2~]~in striatal synaptosomes.)…”
Section: Determination Of Pathway For Ca 2~entry On Activation Of Synmentioning
confidence: 56%
“…5A) or with a mixture of 1 ,uM w-conotoxin MVIIC, 1 ,iiM w-conotoxin GVIA, and 0.2 ,iiM agatoxin TK (Fig. 6A), confirming that the depolarization-induced increases in [Ca2~I, resulted from the opening of voltage-gated Ca2~channels (Nachshen and Blaustein, 1979;Dunlap et al, 1995) largely belonging to the N-, P-, and Qtype family of channels in view of the selectivity of the toxins used (Rivier et al, 1987;Hillyard et al, 1992;Shikata et al, 1995). (In preliminary experiments, we tested a broad variety of Ca2~channel toxin combinations and found that the mixture used in the present study was the most effective in blocking K ±-induced changes in [Ca2~]~in striatal synaptosomes.)…”
Section: Determination Of Pathway For Ca 2~entry On Activation Of Synmentioning
confidence: 56%
“…The mRNA of D/Lpeptides contains codons for L-amino acids and isomerization of one of these amino acids is catalyzed post-translation by specific peptide L/D-isomerases (Bansal et al, 2008;Heck et al, 1996;Jilek et al, 2005;Shikata et al, 1995). This apparently uncommon chirality was revealed in a variety of taxa, reviewed by Kreil (Kreil, 1997) and summarized by Buczek et al (Buczek et al, 2005) and Ollivaux et al (Ollivaux et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the enzyme from Conus snails that catalyzes the vitamin K-dependent formation of the ␥-carboxy glutamic acids present in some venom peptides is highly homologous to the corresponding carboxylase from bovine liver (28,29). Thus, it seems to be surprising that structurally unrelated enzymes catalyze the L-D-isomerization of amino acids in peptide linkage in spider venom (15) and frogs. Evidence indicates that, in both cases, the catalytic mechanism is basically the same (namely, removal of a proton from the ␣-carbon and concomitant addition from the opposite side in an acid-base type of catalysis).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the chirality of a Ser close to the C terminus of a peptide termed -agatoxin IV is inverted. This ''isomerase'' is related to Ser proteases and functions without any added cofactors (14,15).…”
mentioning
confidence: 99%